Chemical composition, antioxidant activity and hepatoprotective potential of Rourea induta Planch. (Connaraceae) against CCl4-induced liver injury in female rats - Milena Kalegari; Carlos Alberto Bruel Gemin; Gabriel Araújo‐Silva; Naira Josele Neves de Brito; Jorge A. López; Sibele de Oliveira Tozetto; Maria das Graças Almeida; Marílis Dallarmi Miguel; Didier Stien; Obdúlio Gomes Miguel (2013)
The aim of this study was to evaluate the flavonoid content of an ethanolic leaf extract from the medicinal plant Rourea induta Planch. (RIEE) and to investigate its hepatoprotective potential and in vivo antioxidant effects.Using samples from carbon tetrachloride-treated Wistar female rats treated orally with or without RIEE, we evaluated the aspartate aminotransferase, alanine aminotransferase, and total bilirubin levels in plasma; the levels of the hepatic oxidative stress markers catalase, superoxide dismutase, glutathione peroxidase, and reduced glutathione in liver homogenates; and the thiobarbituric acid reactive substance levels. A histopathology study was performed. A quantitative analysis of the RIEE extract was performed using high-performance liquid chromatography to evaluate its flavonoid content.Oral administration of RIEE significantly reduced carbon tetrachloride-induced elevations in the levels of plasma markers of hepatic damage and lipid peroxidation. It also rescued histopathologic alterations observed in the liver and levels of oxidative stress markers.RIEE exhibits antioxidant and hepatoprotective activities in vivo, which may be attributable to its flavonoids composition [hyperin (2), quercetin-3-O-β-xyloside (4), quercetin-3-O-α-arabinofuranoside (5), and quercetin (6)].